Mecanismo para garantia de privacidade em redes sociais online - Botelho, Rodrigo Pereira (2011)
The use of online social networks for sharing personal data is becoming increasingly common. To join an online social network, users must agree to the online social networks policies and this generally implies agreeing that all posted data can be used for various purposes, for instance, to improve the service offered by the social network operator. Online social networks generally provide tools to allow users to restrict access to their shared data. However, these access restrictions applies only to social network users, enabling third parties and the social network itself access and use to these data. A data encryption based approach only is insufficient to ensure privacy and preserve the ability of the user to obtain personalized services. This paper presents a mechanism based on a well-known message format coupled with the use of methods for symmetric and asymmetric encryption to extend the privacy in online social networks, ensuring that certain user data types remain private to other network users, third parties and own social network, yet allowing the offering of personalized services. Additionally, a case study using the mechanism in a real online social network and an analysis of the mechanism are presented.